Myanmar : 2013 Article IV Consultation and First Review Under the Staff-Monitored Program. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that recent economic developments in Myanmar have been positive. Growth is estimated to have risen to 6 1\2 percent in FY2012/13 (April-May), driven by gas production, construction and services while inflation climbed to 4.7 percent in March 2013. The external current account deficit is estimated to have widened to about 4 1\2 percent of GDP in FY2012/13, but to have been largely financed by foreign direct investment. The economic outlook remains favorable. Growth is expected to accelerate slightly in FY2013/14, led by rising gas production and investment, including in the transport and telecommunications sectors, and a recovery in agriculture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet